Ahout the bryoflora of La Herrería oakwood (San Lorenzo del Escorial, Madrid) - López, Carmen; Lara García, Francisco; Mazimpaka, Vicente (Botanica Complutensis, 1993)
LOPEZ, C., MAZIMPAKA. V. & LARA, F. 1993. About the bryoflora of La Herrería oakwood. (San Lorenzo de El Escorial, Madrid). Boí. Complutensis 18: 241-249 Ris study deals with the bryoflora of a Que/cus pyrenaica Wiltd. wood, located in one of the most ecologically interesting sites within the province of Madrid. A catalogue of 92 taxa (7 liverworts and 85 mosses) from fíeld-collected saínples, is presented. Five taxa are new or second records for the province. Rey words: Bryoflora, marceseent oak wood, Quercus pyrenaica, Madrid, Spain. Botánica compluiensis 18: 241-249. Edit. Universidad Complutense 1993 242 Carmen López, Vicente Mazinipaka y Francisco Laja